Incidence of Stent Thrombosis after Endovascular Treatment of Iliofemoral or Caval Veins in Patients with the Postthrombotic Syndrome - Sebastian, Tim; Spirk, David; Engelberger, Rolf P.; Dopheide, Jörn F.; Baumann, Frederic A.; Barco, Stefano; Spescha, Rebecca; Leeger, Claudia; Kucher, Nils (Thrombosis and Haemostasis, 2019)
Background Patients with postthrombotic syndrome (PTS) treated with stents are at risk of stent thrombosis (ST). The incidence of ST in the presence and absence of anticoagulation therapy (AT) is unknown. Risk factors are not well understood.Patients and Methods From the prospective Swiss Venous Stent registry, we conducted a subgroup analysis of 136 consecutive patients with PTS. Incidence of ST was estimated from duplex ultrasound or venography, and reported for the time on and off AT. Baseline, procedural, and follow-up data were evaluated to identify factors associated with ST.Results Median follow-up was 20 (interquartile range [IQR] 9–40) months. AT was stopped in 43 (32%) patients after 12 (IQR 6–14) months. Cumulative incidence of ST was 13.7% (95% confidence interval [CI] 7.8–19.6%) and 21.2% (95% CI 13.2–29.2%) during the first 6 and 36 months, respectively. The time-adjusted incidence rate was 11.2 (95% CI 7.7–16.2) events per 100 patient-years, 11.3 (95% CI 7.3–17.3) for the period on, and 11.2 (95% CI 5.3–23.6) for the period off AT. May–Thurner syndrome (MTS) was associated with decreased incidence of ST (hazard ratio [HR] 0.37, 95% CI 0.15–0.91), whereas age < 40 years (HR 2.26, 95% CI 1.03–4.94), stents below the common femoral vein (HR 3.03, 95% CI 1.28–7.19), and postthrombotic inflow veins (HR 2.92, 95% CI 1.36–6.25) were associated with increased incidence.Conclusion The 6-month incidence of ST was considerably high. Beyond 6 months, consecutive annual incidence rates persisted at 4.1 and 3.4% per year thereafter. Patients with higher incidence of ST were younger, had stents below the common femoral vein, postthrombotic leg inflow veins, and less often MTS. Incidence rates for the period on and off AT must be interpreted with caution.Clinical Trial Registration The study is registered on the National Institutes of Health Web site (ClinicalTrials.gov; identifier NCT02433054).
Keywords: anticoagulation; postthrombotic syndrome; venous stent thrombosis; May–Thurner syndrome; ARIVA